Authentic Leadership and Human Resources Role for Future Work - Lucky Setiawan; Willson Gustiawan (Publication Division of International Ecsis Association, 2023)
Authentic leadership is a style of leadership that emphasizes openness, sincerity, and honesty. Authentic leaders cultivate real relationships with their people by instilling trust and building a healthy work environment. Evaluating the publicly stated efforts of one world leader in terms of his ability to demonstrate his authentic leadership attributes during the COVID-19 pandemic response. Using existing literature, this article explores how his attitude has helped or hampered his leadership responsibilities. Furthermore, leadership is intimately tied to human resource management, particularly in terms of reacting to the future of work. The term